The Implementation of The Rotating Trio Exchange Type Cooperative Learning Model In Learning Nahwu - Choiruddin; Imroatus Solikah (ALIF: Journal of Arabic Language and Learning in Focus, 2026)
Learning Nahwu as a foundational component for understanding Arabic often encounters challenges related to limited student engagement and insufficient conceptual comprehension. To address these issues, the Rotating Trio Exchange (RTE) cooperative learning model is introduced as an instructional strategy that emphasizes collaboration and systematic group rotation to enhance interaction and understanding. This study aims to examine the implementation of the RTE model in Nahwu learning and to analyze its impact on students’ learning activities, conceptual understanding, and learning outcomes. Employing a qualitative descriptive approach with a classroom action research design, the study involved 30 second-semester students at STAI KH. Muhammad Ali Shodiq. Data were collected through classroom observations, conceptual understanding tests, interviews, and learning documentation. The findings indicate that the implementation of the RTE model resulted in significant improvements across three key aspects. Student learning activities increased by 78%, reflected in more active participation during group discussions. Students’ conceptual understanding of Nahwu improved by 82% based on evaluation test results, while their collaboration and communication skills developed progressively through structured group rotation. These results demonstrate that the Rotating Trio Exchange cooperative learning model is effectively applied in Nahwu instruction by creating a dynamic collaborative learning environment, enhancing comprehension of Arabic grammatical concepts, and fostering students’ social skills.